Bioelectrical Impedance and Dual-Energy X-Ray Absorptiometry Assessments of Changes in Body Composition Following Exercise in Patients with Type 2 Diabetes Mellitus - Masae Miyatani; Pearl Yang; Scott Thomas; B. Catharine Craven; Paul Oh (Journal of Obesity)
We aimed to compare the level of agreement between leg-to-leg bioelectrical impedance analysis (LBIA) and dual-energy X-ray absorptiometry (DXA) for assessing changes in body composition following exercise intervention among individuals with Type 2 diabetes mellitus (T2DM). Forty-four adults with T2DM, age 53.2±9.1 years; BMI 30.8±5.9 kg/m2 participated in a 6-month exercise program with pre and post intervention assessments of body composition. Fat free mass (FFM), % body fat (%FM) and fat mass (FM) were measured by LBIA (TBF-300A) and DXA. LBIA assessments of changes in %FM and FM post intervention showed good relative agreements with DXA variables (P<0.001). However, Bland-Altman plot(s) indicated that there were systematic errors in the assessment of the changes in body composition using LBIA compared to DXA such that, the greater the changes in participant body composition, the greater the disparity in body composition data obtained via LBIA versus DXA data (FFM, P=0.013; %FM, P<0.001; FM, P<0.001). In conclusion, assessment of pre and post intervention body composition implies that LBIA is a good tool for assessment qualitative change in body composition (gain or loss) among people with T2DM but is not sufficiently sensitive to track quantitative changes in an individual’s body composition.